Voltammetric and microscopic characteristics of MnO2 and silica-MnO2hybrid films electrodeposited on the surface of planar electrodes. (20th May 2019) - Kovalyk, Anastasiia; Tananaiko, Oksana; Borets, Anna; Etienne, Mathieu; Walcarius, Alain
Abstract: The morphological and electrocatalytic properties of ITO and nanostructured carbon screen printed electrodes (nanoSPCE) modified with thin films of MnO2 particles, alone or as hybrid with SiO2, as obtained using electrodeposition techniques, were studied. The time and potential of MnO2 electrodeposition influenced the electrocatalytic properties of the modified electrodes towards H2 O2 . The highest electrocatalytic current was observed at deposition potential E = +0.8 V and deposition time of 10 s MnO2 particles with uniform distribution were obtained onto the electrode surface when prepared under optimal conditions. The nanoSPCE–MnO2 has demonstrated larger effective surface area and faster charge transfer rates compared to ITO–MnO2 . The electrodeposited silica, in addition to MnO2, improved the operational stability of the electrodes without notice able decreasing of their performance. Modified electrodes were used for hydrogen peroxide determination. Graphical abstract: Image 1 Highlights: MnO2 particles were electrodeposited onto ITO and nanostructured C electrodes. Electrocatalytic activity towards H2O2 depends on the deposition conditions. Overcoating with a silica film improves operational and long-term stability. Equimolar amount of ascorbic acid does not interfere on H2O2 detection.